2009
DOI: 10.1007/s12325-009-0058-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different postmenopausal hormone therapy regimens on cerebral blood flow and cognitive functions

Abstract: Different postmenopausal hormone therapy regimens have not revealed any significant effects on either cerebral blood flow or cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These findings suggest that differential expression and regulation of the H 2 S biosynthesis system in different vascular beds have important implications to comprehend the understanding of the cardiovascular protective effects of estrogens. In contrast, ERT has been shown to not significantly affect cerebral blood flow or cognitive function in postmenopausal women (55), and to be associated with a decreased common CA intima-media thickness and arterial stiffness, which are thought to be predictors of cardiovascular diseases in postmenopausal women (56). However, other studies have shown ERT to promote cerebral blood flow and cognitive function in women over 55 years of age (57) and to reduce age-associated increases in common CA stiffness (58).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that differential expression and regulation of the H 2 S biosynthesis system in different vascular beds have important implications to comprehend the understanding of the cardiovascular protective effects of estrogens. In contrast, ERT has been shown to not significantly affect cerebral blood flow or cognitive function in postmenopausal women (55), and to be associated with a decreased common CA intima-media thickness and arterial stiffness, which are thought to be predictors of cardiovascular diseases in postmenopausal women (56). However, other studies have shown ERT to promote cerebral blood flow and cognitive function in women over 55 years of age (57) and to reduce age-associated increases in common CA stiffness (58).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a recent review found that some formularies, such as 17b-estradiol, are associated with more cognitive benefits than others, particularly those that include progesterone compounds [39]. However, other studies failed to find a significant difference between women taking estrogen-only HT compared with those taking a combination of estrogen plus progesterone [48,49]. In the current study, HT users were relatively evenly divided between estrogen-only HT and estrogen plus progesterone HT, and post-hoc analysis did not find any significant differences in language performance between these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focused on vascular responses of postmenopausal women receiving hormone replacement therapy (HRT). Wender et al [12] studied internal carotid artery, Guvenal et al [13] cerebral blood flow, and Huang et al [14] internal carotid and uterine arteries.…”
Section: Introductionmentioning
confidence: 99%